Correlation between Leptin and Free Testosterone Levels in Transfusion-Dependent Thalassemia Male Patients - Lubis, Dian Anindita; Karina Sugih Arto; Heny Syahrini (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Background: Male hypogonadism is a clinical disorder of low testosterone and spermatozoa due to impaired production that can occur at one or more levels in the hypothalamic-pituitary-gonadal (HPG) axis. Apart from iron accumulation, hypogonadism can also occur due to other mechanisms in thalassemia patients, such as the influence of adipose tissue and leptin. The study aimed to assess the relationship between leptin with free testosterone levels and BMI in transfusion-dependent thalassemia. Method: The research design chosen was analytic cross-sectional. The study was conducted at the adult thalassemia polyclinic of Cipto Mangunkusumo General Hospital and Fatmawati General Hospital, during the period July - December 2022. The samples used were male transfusion-dependent thalassemia patients aged over 18 years who were under control at the Thalassemia Polyclinic during the study period. The diagnosis of Thalassemia had been previously established by high-performance liquid chromatography (HPLC) or microcapillary examination. Result: Most patients were major ÃŸ thalassemia (87.8%), while HbE ÃŸ thalassemia was only 12.1%. Age distribution was with a median of 23 years (minimum-maximum 18-42 years). The clinical symptoms of hypogonadism were erectile dysfunction and decreased libido (12.1% and 9%, respectively). From body mass index examination were underweight 18 (54,5%), normal weight 13 (39,5%), overweight 1 (3%), and obese 1 (3%). Of the 33 transfusion-dependent thalassemia patients, 95% did not reach puberty according to their age (Tanner stage V). Conclusion: There is an association significantly between leptin levels with free testosterone and body mass index in transfusion-dependent thalassemia men.